Theoretical Calculation and Experimental Analysis on Initial Shock Pressure of Borehole Wall under Axial Decoupled Charge - Xiaoming Lou; Zhenchang Wang; Bigang Chen; Jin Yu (Shock and Vibration)
This paper attempts to calculate the exact initial shock pressure of borehole wall induced by the blasting with axially decoupled charge. For this purpose, Starfield superposition was introduced considering the attenuation and superposition of blasting pressure, and the theoretical solution of initial borehole wall pressure was obtained for the upper and middle air-decked charging structures. Then, the explosive pressure field around the borehole was measured by cement mortar models and a dynamic pressure test system, and the pressures at multiple measuring points were simulated with numerical models established by ANSYS/LS-DYNA. The results show that the deviations between simulated and theoretical pressures are smaller than 10%, indicating the reliability of the theoretical formula derived by Starfield superposition. For the upper air-decked charging structure, the initial shock pressure of the charging section followed a convex distribution, with the peak value near the charge centre. With the increase in the distance from the charging section, the borehole wall shock pressure in the air gap underwent a sharp decline initially before reaching a relatively constant level. The minimum pressure was observed at the hole collar. For the middle air-decked charging structure, the pressures at both ends of the charging section obeyed a convex distribution, with the peak value near the charge centre. Finally, the author optimized air-decked charging structure of periphery boreholes within Grade III surrounding rocks of Banjie tunnel, China, and proved the enhancement effect of the theoretical findings on smooth blasting. The research findings provide valuable references to the theoretical and experimental calculation of air column length and other key parameters of air-deck blasting and shed new light on the charging structure determination of smooth blasting and blasting vibration control for the excavation of large-section, deep mining roadways.